Avaliação do desempenho de um ciclone stairmand adaptado com bicos injetores de água - Chiabai Junior, João (Universidade Federal de São Carlos, 2014)
The collection efficiency and costs of implementation and operation are the main factors considered in the use of equipment for the separation of particulate matter in the gas. The cyclone is commonly employed industrially by low costs, however its use is limited due to the low efficiency in collecting particles smaller than 5 μm. The increase of conventional cyclone with nozzles water led to an improvement in its collection efficiency. This work experimentally investigated the performance of a wet cyclone in the removal of phosphate rock with median diameter of 4.66 μm. The cyclone was adapted with 8 water injectors nozzles of range type. The concentrations of particles in the entrance and exit of equipment were obtained by isokinetic sampling. The ratio of the flow of liquid / gas (L/G) was varied from 0.65 to 2.20 L/m3 to 3 different nozzle configurations. The outlet temperature decreased compared to entry with increase of the ratio L/G. Have the relative humidity of the gas increased with increasing L/G. The cyclone dry operating had an average efficiency of 76.7% and the best average efficiency the wet was 85.3%. The fractional collection efficiency was determined only for the operating condition that resulted in the best overall efficiency. The adaptation of the cyclone Stairmand with water injectors nozzles resulted in an improvement of 8.6% in the overall collection efficiency.
Keywords: Separação (Tecnologia); Ciclone; Lavador (Tecnologia química); Gás - escoamento; Material particulado; ENGENHARIAS::ENGENHARIA QUIMICA